PENGEMBANGAN EVALUASI PEMBELAJARAN MENGGUNAKAN EDUCAPLAY PADA PEMBELAJARAN IPAS MATERI INDONESIAKU KAYA ALAMNYA - Syiffa Nur Hofifah; Indriyani; Rini Sri Indriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Development of Learning Evaluation Using Educaplay in IPAS Learning My Indonesian Rich Material in Nature. This research uses an R&D (Research and Development) approach at Ciawi State Elementary School 03 Bogor Regency. The research subject was a class V student of Ciawi State Elementary School 03 consisting of 25 students. This research was conducted in the even semester of the 2024/2025 academic year. The purpose of this study is to develop a Learning Evaluation Using Educaplay in the Learning of Science Materials Indonesiaku Kaya Alam to determine its feasibility and effectiveness. This research uses the ADDIE (Analysis, Design, Development, Implemantion, Evaluation) method. In this study, a validation test was used for experts, namely media experts, linguists, and material experts. To develop the effectiveness of cognitive ability results, students measured with pre-test and post-test scores.To develop and improve Learning Evaluation using Educaplay, a response from students and teachers is needed. The results of the evaluation by media experts were 98% with the criterion of "Very Feasible", linguists obtained a percentage of 96% with the criterion of "Very Feasible", material experts (Lecturers) obtained a percentage of 94% with the criterion of "Very Feasible" and material experts (Teachers) obtained a percentage of 98% with the criterion of "Very Feasible." The results of the pre-test and post-test in the students showed that the N-Gain score at kels V reached 0.89, included in the "High" category with a total of 25 with the highest pre-test score of 85 and the lowest 50 with an average of 67.36. Meanwhile, the post-test N-Gain score with the highest score of 100 and the lowest score of 85 has an average of 96.28. So that students' abilities are improved "Effective" after using learning evaluation using Educaplay. The results of the student response questionnaire obtained a percentage result of 93.52% with the criterion of "Very Feasible", and the results of the teacher response questionnaire showed a percentage of 98% with the criterion of "Very Feasible." Thus, it can be concluded that the evaluation of defense using Educaplay is feasible and effective for students to use in learning activities in elementary schools.